China's K-12 teacher qualification system - Dani Surya Lee (Jurnal Penelitian dan Evaluasi Pendidikan, 2019)
A strict teacher qualification system is vital to ensure a steady stream flow of high-quality human resources. In 1993, the People's Republic of China established the Teacher Law demanding that teachers must have legal status and qualifications. It has put into effect a system of qualification that could determine the readiness of K-12 teacher candidates to be practitioners of education. This country's teacher qualification system has experienced changes and adaptations until it has reached the current form in 2016's Teacher Qualification Examination, as more than a tool merely for formality or evaluation of rote learning, but an actual assessment of pre-service teachers' knowledge and abilities to conduct classroom teaching in authentic settings. This paper introduces this qualification examination system, while also mentioning some important and distinguishable aspects of teachers' situations in China, in the hope that it will shed some light on how this Asian giant is currently conducting its education.